Loss of ADAMTS5 enhances brown adipose tissue mass and promotes browning of white adipose tissue via CREB signaling - Dries Bauters; Mathias Cobbaut; Lotte Geys; Johan Van Lint; Bianca Hemmeryckx; H. Roger Lijnen (Elsevier, 2017)
Objective: A potential strategy to treat obesity - and the associated metabolic consequences - is to increase energy expenditure. This could be achieved by stimulating thermogenesis through activation of brown adipose tissue (BAT) and/or the induction of browning of white adipose tissue (WAT). Over the last years, it has become clear that several metalloproteinases play an important role in adipocyte biology. Here, we investigated the potential role of ADAMTS5. Methods: Mice deficient in ADAMTS5 (Adamts5−/−) and wild-type (Adamts5+/+) littermates were kept on a standard of Western-type diet for 15 weeks. Energy expenditure and heat production was followed by indirect calorimetry. To activate thermogenesis, mice were treated with the β3-adrenergic receptor (β3-AR) agonist CL-316,243 or alternatively, exposed to cold for 2 weeks. Results: Compared to Adamts5+/+ mice, Adamts5−/− mice have significantly more interscapular BAT and marked browning of their subcutaneous (SC) WAT. Thermogenic pathway analysis indicated, in the absence of ADAMTS5, enhanced β3-AR signaling via activation of the cAMP response element-binding protein (CREB). Additional β3-AR stimulation with CL-316,243 promoted browning of WAT in Adamts5+/+ mice but had no additive effect in Adamts5−/− mice. However, cold exposure induced more pronounced browning of WAT in Adamts5−/− mice. Conclusions: These data indicate that ADAMTS5 plays a functional role in development of BAT and browning of WAT. Hence, selective targeting of ADAMTS5 could provide a novel therapeutic strategy for treatment/prevention of obesity and metabolic diseases.